2003
DOI: 10.1111/1539-6924.00380
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Multimedia Models Assessing Exposure to PAHs—The SOLEX Study

Abstract: Polluted soils have become a public health problem. While population exposure to soil pollutants is generally quantified using multimedia models, their estimations have not been validated, and studies that attempted to do so are scarce. The objective of the SOLEX study was to compare the predictions of pyrene exposure levels (converted into 1 hydroxypyrene) computed by several models with the results of urinary 1-hydropyrene (1-HOP) assays among 110 employees working at three sites polluted during their past u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Results are similar to those from several other studies (Brock et al , 2003; Dor et al , 2003; Thiessen et al , 1997; Mills et al , 1997; CMHC, 1997), which suggested that at a smaller scale, it is the assumptions an assessor makes, based on his or her judgment, which is of primary importance in the assessment of exposure and risk. At a larger scale, judgment and policy rather than science are responsible for choices such as that of TRV, which result in the greatest variability among agencies and on the assessment of risk altogether.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results are similar to those from several other studies (Brock et al , 2003; Dor et al , 2003; Thiessen et al , 1997; Mills et al , 1997; CMHC, 1997), which suggested that at a smaller scale, it is the assumptions an assessor makes, based on his or her judgment, which is of primary importance in the assessment of exposure and risk. At a larger scale, judgment and policy rather than science are responsible for choices such as that of TRV, which result in the greatest variability among agencies and on the assessment of risk altogether.…”
Section: Discussionsupporting
confidence: 88%
“…Dor et al (2003) compared exposure estimates from four multimedia human exposure models: AERIS (Canada), CalTOX (United States), CLEA (United Kingdom), and HESP (The Netherlands). Exposure to the PAH pyrene was estimated using multiple exposure scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…This biomarker of personal PAH exposure (which measures the metabolite of pyrene, a common component of PAH mixtures and was at 2 to 4 time greater levels than BaP levels in samples) was extensively used in occupational settings, where worker exposures to pyrene in air and via the skin were found in good agreement with measurements of urinary 1-OHP (Bouchard & Viau, 1999;Brandt & Watson, 2003;Dor et al, 2003). Environmental measurements were also reported in various subpopulations (Gundel et al, 1996;Jongeneelen, 2001) and in large-scale population surveys in the United States (NHANES, 2004;Huang et al 2004).…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Briefly, the CalTOX model considers chemical transformation in the environment and uses biotransfer and bioconcentration factors. The CalTOX model has been widely used for environmental contaminant distributions and multimedia exposure and risk assessments . The model can estimate direct inhalation exposure from environmental releases to ambient air and also track indirect exposures through food or water ingestion attributable to the environmental releases (e.g., surface water) in a particular study area.…”
Section: Methodsmentioning
confidence: 99%